Lymph node metastasis between sternocleidomastoid and sternohyoid muscle in clinically node‐positive papillary thyroid carcinoma. Issue 8 (28th August 2012) - Sun, Guohua; Wang, Yu; Zhu, Yongxue; Wang, Yulong; Xu, Kuan; Wei, Wenjun; Li, Hui; Lu, Zhongwu; Ji, Qinghai
Abstract Background There have been few reports on lymph node metastasis between sternocleidomastoid and sternohyoid muscle (originally LNSS) in clinically node positive (cN+) papillary thyroid carcinoma (PTC). Therefore, our objective was to investigate the significance of LNSS metastasis. Methods A total of 115 patients with cN+ PTC underwent a neck dissection with LNSS, as a separate pathologic specimen to be analyzed for the correlation between LNSS and sex, age, tumor size, tumor site, initial or reoperative treatment, lateral cervical lymph nodes, and central compartment metastasis. Results The positive rate of LNSS was 22.6%. LNSS metastasis was correlated with a primary site in the inferior pole, the lateral nodal metastasis, level III and level IV nodal metastasis, but not with other clinical parameters. Conclusion In cN+ PTC, especially a primary site in the inferior pole, level III and/or level IV metastasis, attention should be given to excising the nodal tissue in LNSS. © 2012 Wiley Periodicals, Inc. Head Neck, 2013